2006
DOI: 10.1007/11753810_57
|View full text |Cite
|
Sign up to set email alerts
|

On the Stability of End-Point-Based Multimedia Streaming

Abstract: Abstract. In this paper we propose an analytical model of a resilient, tree-based end-node multicast streaming architecture that employs path diversity and forward error correction for improved resilience to node churns and packet losses. Using the model and via simulations we study the performance of this architecture in the presence of packet losses and dynamic node behavior. We show that the overlay can distribute data to nodes arbitrarily far away from the root of the trees as long as the loss probability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The model does not take into account the correlations between packet losses in the Internet. Nevertheless, it can be extended to heterogeneous and correlated losses by following the procedure presented in [13] for the minimum breadth trees. Losses occurring in bursts on the output links of the nodes influence the performance of the overlay if several packets of the same block are distributed over the same tree, that is, if n > t. Bursty losses in the backbone influence the performance if packets of different distribution trees traverse the same bottleneck.…”
Section: Discussion Of the Assumptionsmentioning
confidence: 99%
See 4 more Smart Citations
“…The model does not take into account the correlations between packet losses in the Internet. Nevertheless, it can be extended to heterogeneous and correlated losses by following the procedure presented in [13] for the minimum breadth trees. Losses occurring in bursts on the output links of the nodes influence the performance of the overlay if several packets of the same block are distributed over the same tree, that is, if n > t. Bursty losses in the backbone influence the performance if packets of different distribution trees traverse the same bottleneck.…”
Section: Discussion Of the Assumptionsmentioning
confidence: 99%
“…Losses occurring in bursts on the output links of the nodes influence the performance of the overlay if several packets of the same block are distributed over the same tree, that is, if n > t. Bursty losses in the backbone influence the performance if packets of different distribution trees traverse the same bottleneck. The analysis in [13] showed that loss correlations on the input links and heterogeneous losses slightly decrease the performance of the overlay.…”
Section: Discussion Of the Assumptionsmentioning
confidence: 99%
See 3 more Smart Citations